NAVIGATING THE HUMAN-WILD PIG CONFLICT IN TAMIL NADU: ASSESSING THE DAMAGE AND EXPLORING SOLUTIONS FOR KRISHNAGIRI DISTRICT - Tisdel, B; Naresh, G (International Journal of Allied Sciences (IJAS), 2022)
The rising wild pig population in India, coupled with stagnant forest areas, has led to an increase in human-wild pig conflict (HWPC), particularly in Tamil Nadu. This case study examines the situation in Krishnagiri district, where farmers and their families face crop damage, financial loss, and even physical injury due to the presence of wild pigs on their land. By exploring the reasons for the intrusion, such as altered cropping patterns and increased wild pig populations, the study aims to develop a better understanding of local attitudes towards the conflict and propose effective mitigation strategies. These include solar fencing, wire net fencing, and the use of modern ICT tools to drive away the intruding wild pigs, helping to reduce the negative impact of HWPC on the agricultural community